Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1519/jsc.0000000000002489
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Bobsled Pushing Ability From Various Combine Testing Events

Abstract: The requisite combination of speed, power, and strength necessary for a bobsled push athlete coupled with the difficulty in directly measuring pushing ability makes selecting effective push crews challenging. Current practices by USA Bobsled and Skeleton (USABS) utilize field combine testing to assess and identify specifically selected performance variables in an attempt to best predict push performance abilities. Combine data consisting of 11 physical performance variables were collected from 75 subjects acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…During a run, injuries are more frequent at the start, with athletes at risk of hamstring strains due to the requisite combination of speed, power, and strength necessary to push the sled efficiently. 23 Soft tissue injuries can occur at the initial running phase while getting into the sled or with team member's footwear spikes. Riding down the bobsled, spinal disk herniations and nerve root compression can result from the strong forces applied on the spine.…”
Section: Bobsled (Or Bobsleigh)mentioning
confidence: 99%
“…During a run, injuries are more frequent at the start, with athletes at risk of hamstring strains due to the requisite combination of speed, power, and strength necessary to push the sled efficiently. 23 Soft tissue injuries can occur at the initial running phase while getting into the sled or with team member's footwear spikes. Riding down the bobsled, spinal disk herniations and nerve root compression can result from the strong forces applied on the spine.…”
Section: Bobsled (Or Bobsleigh)mentioning
confidence: 99%
“…The three different events in bobsleigh all highlighted the importance of a top-ranked start in relation to finish ranking. Previous research suggests that power, speed and strength variables are decisive in bobsleigh team selection (Osbeck et al, 1996;Tomasevicz et al, 2018). Therefore, a physical development program focusing on the suggested variables may be recommended to improve start performance in bobsleigh.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…The start performance in respective sliding sport heavily determines initial velocities, which may influence the remaining velocities and ultimately finishing time. The emphasis on starts in sliding sports is evident in the number of studies that concentrate on variables surrounding start performance in bobsleigh (Dias Lopes & Alouche, 2016;Osbeck et al, 1996;Peeters et al, 2019;Tomasevicz et al, 2018), luge (Crossland et al, 2012;Lembert et al, 2011;Platzer et al, 2009) and skeleton (Bullock et al, 2008;Colyer et al, 2017;Colyer et al, 2018aColyer et al, , 2018b. Studies researching overall race performance was only found to have been published twice across all three sports (Morlock & Zatsiorsky, 1989;Zanoletti et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, in studies related to the use of DaeDo electronic body protectors to trigger scoring in Taekwondo, there is a lack of research on key biomechanical factors related to the scoring values of the front roundhouse kick. In other sports, research on key biomechanical factors has been able to determine the primary factors that determine competition results (Bullock et al, 2009;Crossland et al, 2011;Tomasevicz et al, 2020). It is hypothesized that there is relatively little attention given to the relationship between the value of effective scoring and the kinematic and kinetic characteristics of the kicking motion when using electronic protectors to trigger valid scoring.…”
Section: Introductionmentioning
confidence: 99%